What do women want in pharmacy-based HIV prevention services during pregnancy? Developing attributes and levels for a discrete choice experiment in Western Kenya - Melissa Latigo Mugambi; Annabell Dollah; Rosebel Ouda; Nancy Oyugi; Ben O. Odhiambo; Mary M. Marwa; Judith Nyakina; John Kinuthia; Bryan J. Weiner; Grace John-Stewart; Ruanne Vanessa Barnabas; Brett Hauber (AIDS Research and Therapy)
Abstract Background The delivery of HIV prevention services (e.g., HIV testing, pre-exposure prophylaxis (PrEP) initiation and refills, and STI testing) in community pharmacies could address clinic barriers faced by pregnant women such as extended travel and wait times. We conducted a qualitative study in Western Kenya to select and prioritize attributes and levels for a discrete choice experiment (DCE) to design pharmacy-based HIV prevention services for pregnant women. Methods We began by identifying a comprehensive list of attributes and levels relevant to women considering HIV prevention during pregnancy. This list was informed by recommended HIV prevention interventions for pregnant women, our objective to design services for pharmacy settings, and attributes identified in the literature as important for other populations when choosing HIV and pharmacy-based services. From March to November 2022, we recruited participants using stratified purposeful sampling and collected qualitative data through seven focus group discussions with women, four with health providers, and eight individual interviews with technical experts. Interviews were audio-recorded, translated, transcribed, and summarized in debrief reports. We conducted debriefing meetings and analyzed these reports to identify and refine the essential attributes that would influence decisions to access HIV prevention services from a pharmacy during pregnancy. Results We initially identified twelve potential attributes that were evaluated during the focus groups. Five attributes were eliminated based on ranking exercises with women and health providers. Additional attributes suggested during the focus groups were ranked low by participants or not mentioned frequently enough and, therefore, not included. We finalized and refined levels for each attribute using insights from the literature, participant feedback, and design considerations. The study identified seven attributes: service location, type of HIV test, STI testing availability, partner HIV testing availability, PrEP availability, service access methods (e.g., appointment versus walk-ins), and service fee. Conclusions This study was the first step in data collection toward defining attributes and levels for a DCE survey and successfully identified seven preliminary attributes and levels. Pre-testing and pilot testing activities further explored the feasibility and understanding of the attributes and levels.